In Search of an Ideal Test for Diagnosis and Prognosis of Kala-azar - Singh, Dharmendra P; Goyal, Rahul K; Singh, Rahul K; Sundar, S; Mohapatra, Tribhuban M (Journal of Health, Population and Nutrition, 2010)
The latex agglutination test (KAtex), direct agglutination test (DAT), and the rK39 immuno-chromatographic strip test (dipstick test) were evaluated for their role in the diagnosis and prognosis of visceral leishmaniasis (kala-azar) in India. Sera and urine samples from 455 subjects - 150 confirmed visceral leishmaniasis cases, 160 endemic controls, 100 non-endemic controls, and 45 other febrile diseases - were included in the study. The sensitivity of the KAtex, DAT, and rK39 strip test was 87% [95% confidence interval (CI) 80-96], 93.3% (95% CI 88-100), and 98% (95% CI 93-100) respectively. The specificity of these tests was 98% (95% CI 93-100), 93% (95% CI 87-100), and 89% (95% CI 82-97) for the KAtex, DAT, and rK39 strip test respectively. Fifty cases were followed up and subjected to the KAtex, DAT, and rK39 strip test after 30 days of successful treatment. The DAT and rK39 strip test showed positive results in all the 50 cases whereas the KAtex showed no positive reaction in any case. Based on the results, it is concluded that the sensitivity and specificity of the DAT and rK39 strip test are comparable but the greater convenience of use of the strip test makes it a better tool for the diagnosis of visceral leishmaniasis in the peripheral areas of endemic regions whereas the sensitivity of the KAtex needs to be improved to promote its use as a first-line diagnostic test in the field-setting. It may be used for the prognosis of the disease as antigen becomes undetectable in urine after 30 days of the completion of the treatment. Alternatively, it can be used as an adjunct with rK39 for sero-epidemiological surveys. Key words: Diagnosis, Laboratory; Direct agglutination test; KAtex; rK39 strip test; Visceral leishmaniasis; India DOI: 10.3329/jhpn.v28i3.5557 J HEALTH POPUL NUTR 2010 Jun;28(3):281-285